Waist to hip ratio in Cardiovascular Disease Risk : A Review of the Literature - Destra, Edwin; Anggraeni, Natasha; Firmansyah, Yohanes; Santoso, Alexander Halim (MAHESA : Malahayati Health Student Journal, 2023)
ABSTRACT The World Health Organisation (WHO) defines obesity and overweight as a medical condition characterized by the abnormal accumulation of fat. While body mass index (BMI) is commonly used to measure obesity, it has limitations in accounting for differences in body fat distribution. The aim of this study is to compare the effects of body mass index and waist-to-hip ratio on the likelihood of developing cardiovascular disease. Various search methods, including indexed sources from Google Scholar, were used to access a diverse range of literature published in the last ten years. The review employed deductive and inductive reasoning to compile and extract relevant information. Deductive reasoning was used to establish a theoretical framework and identify concepts related to waist-to-hip ratio (WHR) and cardiovascular disease (CVD). Inductive reasoning was then applied to analyse the literature and draw conclusions based on the accumulated evidence. The study found that waist-to-hip ratio is a valuable indicator of cardiovascular disease risk in people of all ages, regardless of their body mass index. It is particularly useful when other metabolic risk factors such as diabetes, lipoprotein abnormalities, smoking, and hypertension are present. This approach is especially beneficial for identifying patients who may be at risk of cardiovascular disease despite having a normal BMI. Waist-to-hip ratio provides additional insights into central adiposity, which has been linked to various metabolic abnormalities and an increased risk of cardiovascular disease. Keywords: Obesity, Waist-to-Hip Ratio, Body Mass Index, Central Adiposity, Cardiovascular Risk